THE EFFECTIVENESS OF ROLE PLAY TECHNIQUE IN IMPROVING SPEAKING ABILITY TO THE TENTH GRADE STUDENTS OF SMAN 3 PALEMBANG - Andinny Sylvia Putri (Global Expert: Jurnal Bahasa dan Sastra, 2016)
This study was aimed to see whether or not role play technique was effective to improve students’ speaking ability. The research design selected wasnon–equivalent control group design. The population of the study was all tenth grade students at SMA Negeri 3 Palembang. Purposive sampling was used to select the sample of the study in which 20 students belong to the experimental group and 20 students belong to the control  group.There was a significant difference mean scores before and after they were exposed to role play technique (to 39.511, p<0.05) and the tt was 2.0244 there was a significant difference in students’ test scores between the students who were taught through role play technique and those who were not. The research finding revealed that role play technique was effective to improve students’ writing ability. these finding were also supported by the significant improvement  in speaking ability between the in term of the four aspects of speaking (pronounciation, vocabulary, grammar and fluency) (p=0.000<0.005). The result of the pre-test and post-test showed that role play was very helpful for the students in improving their speaking ability .The study was expected to yield a better quality of speaking Key words : speaking, role play